1999
DOI: 10.1097/00005373-199907000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Arterial Shunts To Maintain Limb Perfusion after Arterial Injury

Abstract: Shunts provided adequate flow in this model of extremity trauma. Correctly placed shunts stayed patent for 24 hours, without anticoagulation, if shunt placement followed resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 14 publications
1
29
1
9
Order By: Relevance
“…The internal diameter of these shunts is sufficient to maintain distal blood flow at approximately 50% of normal which provides adequate oxygenation given compensatory local increases in oxygen extraction. 15 This diameter is not, however, sufficient to produce palpable pedal pulses in most instances. Nonetheless, at least biphasic distal flow through arterial shunts should be detectable by hand-held Doppler.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The internal diameter of these shunts is sufficient to maintain distal blood flow at approximately 50% of normal which provides adequate oxygenation given compensatory local increases in oxygen extraction. 15 This diameter is not, however, sufficient to produce palpable pedal pulses in most instances. Nonetheless, at least biphasic distal flow through arterial shunts should be detectable by hand-held Doppler.…”
Section: Discussionmentioning
confidence: 98%
“…These benefits of deep shunt insertion must be considered in light of the potential for iatrogenic injury and thrombosis if side branches are entered or the end of the shunt comes to lie against the vessel wall. 15 This appeared to be the primary factor producing thrombosis of superficial femoral artery and vein shunts placed in a multiply traumatized 14-year-old Iraqi patient (patient 17). The distal portion of the shunt in this case came to lie relatively close to the vascular trifurcation despite the proximal ends lying as far proximal as they could be passed without resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparinization was not used in either report and, in fact, it may not be necessary. A recent animal study in pigs found that 13 of 16 common iliac artery shunts remained patent without heparinization for 24 h [10]. Significantly, seven of eight shunts remained patent for that period in a group of animals in shock, in which the shunt was placed 1 h after induction of limb ischemia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although its use is generally recommended if not contraindicated, several authors have described successful outcomes in the absence of systemic anticoagulation 41,48 . It has been shown in an animal model that shunt patency can be maintained for at least 24 h in the absence of anticoagulation if the device is correctly placed technically 49 . When dealing with combined arterial and venous injuries, where the vein is ligated in the setting of the patient in extremis, four-compartment fasciotomy at the initial operation is mandatory to prevent subsequent compartment syndrome and its inherent complications.…”
Section: Extremity Injurymentioning
confidence: 99%